Precision medicine in pantothenate kinase-associated neurodegeneration - Mónica Alvarez-Cordoba (Neural Regeneration Research, 2019)
Neurodegeneration with brain iron accumulation is a broad term that describes a heterogeneous group of progressive and invalidating neurologic disorders in which iron deposits in certain brain areas, mainly the basal ganglia. The predominant clinical symptoms include spasticity, progressive dystonia, Parkinson’s disease-like symptoms, neuropsychiatric alterations, and retinal degeneration. Among the neurodegeneration with brain iron accumulation disorders, the most frequent subtype is pantothenate kinase-associated neurodegeneration (PKAN) caused by defects in the gene encoding the enzyme pantothenate kinase 2 (PANK2) which catalyzed the first reaction of the coenzyme A biosynthesis pathway. Currently there is no effective treatment to prevent the inexorable course of these disorders. The aim of this review is to open up a discussion on the utility of using cellular models derived from patients as a valuable tool for the development of precision medicine in PKAN. Recently, we have described that dermal fibroblasts obtained from PKAN patients can manifest the main pathological changes of the disease such as intracellular iron accumulation accompanied by large amounts of lipofuscin granules, mitochondrial dysfunction and a pronounced increase of markers of oxidative stress. In addition, PKAN fibroblasts showed a morphological senescence-like phenotype. Interestingly, pantothenate supplementation, the substrate of the PANK2 enzyme, corrected all pathophysiological alterations in responder PKAN fibroblasts with low/residual PANK2 enzyme expression. However, pantothenate treatment had no favourable effect on PKAN fibroblasts harbouring mutations associated with the expression of a truncated/incomplete protein. The correction of pathological alterations by pantothenate in individual mutations was also verified in induced neurons obtained by direct reprograming of PKAN fibroblasts. Our observations indicate that pantothenate supplementation can increase/stabilize the expression levels of PANK2 in specific mutations. Fibroblasts and induced neurons derived from patients can provide a useful tool for recognizing PKAN patients who can respond to pantothenate treatment. The presence of low but significant PANK2 expression which can be increased in particular mutations gives valuable information which can support the treatment with high dose of pantothenate. The evaluation of personalized treatments in vitro of fibroblasts and neuronal cells derived from PKAN patients with a wide range of pharmacological options currently available, and monitoring its effect on the pathophysiological changes, can help for a better therapeutic strategy. In addition, these cell models will be also useful for testing the efficacy of new therapeutic options developed in the future.